2020
DOI: 10.3390/ijerph17144997
|View full text |Cite
|
Sign up to set email alerts
|

Manipulative Therapy Plus Ankle Therapeutic Exercises for Adolescent Baseball Players with Chronic Ankle Instability: A Single-Blinded Randomized Controlled Trial

Abstract: Manipulative therapies and exercises are commonly used for the management of chronic ankle instability (CAI), but there is no evidence regarding the efficacy of high-velocity low-amplitude manipulation (HVLA) in addition to ankle therapeutic exercise to improve CAI in adolescent baseball players (ABP). To compare the effects of HVLA plus ankle therapeutic exercise and ankle therapeutic exercise alone on ankle status, pain intensity, pain pressure threshold (PPT), range of motion (ROM) of the ankle joint, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Muscle strength peaks in an individual’s 20s or 30s, decreases 1.5% per year in one’s 50s to 60s, and decreases 3% per year thereafter [ 6 , 7 ]. A greater decline occurs in the lower extremities than in the upper extremities, creating a functional decrease in the ankle joint stabilizers such as the tibialis anterior (TA), gastrocnemius, and soleus [ 8 , 9 , 10 , 11 ]. The TA is an ankle stabilizer and support of the peroneus muscle that maintains balance and locomotion [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle strength peaks in an individual’s 20s or 30s, decreases 1.5% per year in one’s 50s to 60s, and decreases 3% per year thereafter [ 6 , 7 ]. A greater decline occurs in the lower extremities than in the upper extremities, creating a functional decrease in the ankle joint stabilizers such as the tibialis anterior (TA), gastrocnemius, and soleus [ 8 , 9 , 10 , 11 ]. The TA is an ankle stabilizer and support of the peroneus muscle that maintains balance and locomotion [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors confirm that this manipulative effect does not always have a sufficiently large positive effect on the functional segments, which, for example, is very important for athletes in terms of the optimal amount of movement in a particular segment. Thus, the researchers confirm that in addition to the manipulative effects on the joints, other manipulative effects on the surrounding tissues (massage, active stretching, exercises) are needed to optimize the volume of movement in the larger segment (Schmid, Brunner, Wright & Bachmann, 2008;Sharma et al, 2012;Pedak et al, 2019;Gouttebarge et al, 2017;Nagy et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…High-velocity, low-amplitude (HVLA) manipulation has been studied for its effects on athletes' mobility and stability. A randomized pilot study found that HVLA applied to the thoracic spine increased spine mobility, but this increase in mobility did not lead to improved gait initiation performance, such as speed and step length (Ditcharles, Yiou, Delafontaine & Hamaoui, 2017);Shin, Kim, Jung, Cho, & Hahm, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is expensive and has high sensitivity but low specificity (Kuijs et al ., 2015; Zhou et al, 2018), and PET-computed tomography (PET-CT) has low sensitivity and high specificity (Marino et al, 2020). While ultrasound has high sensitivity and specificity (Garcia Fernandez et al ., 2011; Shin et al, 2020). Ultrasound, with its noninvasive, real-time and low-cost advantages, has become the most commonly used modality for preoperative evaluation of breast masses and axillary lymph nodes.…”
Section: Introductionmentioning
confidence: 99%